Towards digital interaction: How an incumbent company creates value through the digital platform - Hämäläinen, Aino (My University, 2022)
The digital interaction between businesses and customers has grown considerably in recent years. The Covid-19 pandemic has also contributed to this, prompting companies to rethink their customer-facing strategy. Companies have developed more digital platforms for their business in response to the digital communications revolution. Therefore, the purpose of this study is to explore how an incumbent company creates value through a digital platform. The study’s first objective is to examine what value is created for the company through the digital platform and what value is proposed to the customer. The second objective is to explore how value can be created for the company and value propositions realized for the customer. The third objective is to examine the challenges of creating value for the company and creating value propositions for the customer on a digital platform. The theoretical part of the study focuses on value creation, value propositions, and value co- creation from a service logic perspective. Secondly, the theoretical part analyses the digital platform and the difference between the value creation of the platform business and the pipe- line business model, as well as the value creation activities and value creation enablers in the context of the digital platform. Finally, the theory section will look more at the challenges as- sociated with the digital platform. The methodological part of the study describes how the study was conducted as a qualitative case study and how the data was collected through semi- structured interviews. The methodology section describes how the study results were analyzed using content analysis and conclude with an analysis of the reliability of the study. The study results showed that the company creates value for itself through the digital platform by reaching a large group of customers simultaneously, from anywhere, at any time, and in a time-saving way. Overall, the platform creates value for the company because it facilitates the overall interaction with customers. The company also creates value through the data collected through the platform to understand customer needs better. The study findings revealed that the company's value proposition to customers is to provide inspirational, educational, and experience value through the platform. In addition, the company proposes as a value proposi- tion that the platform enables the co-creation of value by facilitating mutual interaction through the platform's interactive activities. The results revealed various challenges to creating value through the platform. For example, attracting and keeping customers on the platform, building a professional team, and finding the right service provider were identified as challenges on a company's digital platform.
Keywords: value creation; digitalisation; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|